ANALYSIS OF MATHEMATICAL NUMERACY SKILLS ON LINE AND ANGLE MATERIAL IN CLASS VII IN TERMS OF EXTROVERTED INTROVERTED AND AMBIVERT PERSONALITIES - Zakaria, Muhammad Hilmi; Azis, Mohammad (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2024)
This research aims to analyze the mathematical numeracy abilities of class VII students with introverted, extroverted and ambivert personalities at SMP Negeri 2 Semarang. The method used was descriptive qualitative with research subjects consisting of 34 students, one student was selected from each personality category based on a questionnaire with 70 question items. The results of the questionnaire showed AAE (introvert), LPA (extrovert), and JRA (ambivert) students as research subjects. Mathematical numeracy ability tests and interviews were carried out to test the validity of the test results through technical triangulation. Indicators of mathematical numeracy abilities include the use of mathematical numbers and symbols, analysis of information in the form of tables, graphs and charts, as well as interpretation of analysis results for decision making. The results showed that introvert and ambivert students met all indicators of numeracy ability, while extrovert students did not. Introvert students can solve problems well, extrovert students tend to be in a hurry and lack details, while ambivert students show quite good results but there are still some answers that are less detailed. This research concludes that mathematical numeracy abilities vary based on student personality.